Grappling with key questions about assessment of the Health Advocate role - LaDonna, Kori A; Kahlke, Renate; Scott, Ian; van der Goes, Theresa; Hubinette, Maria (Canadian Medical Education Journal, 2023)
Introduction: Although the CanMEDS framework sets the standard for Canadian training, health advocacy competence does not appear to factor heavily into high stakes assessment decisions. Without forces motivating uptake, there is little movement by educational programs to integrate robust advocacy teaching and assessment practices. However, by adopting CanMEDS, the Canadian medical education community endorses that advocacy is required for competent medical practice. It’s time to back up that endorsement with meaningful action. Our purpose was to aid this work by answering the key questions that continue to challenge training for this intrinsic physician role. Methods: We used a critical review methodology to both examine literature relevant to the complexities impeding robust advocacy assessment, and develop recommendations. Our review moved iteratively through five phases: focusing the question, searching the literature, appraising and selecting sources, and analyzing results. Results: Improving advocacy training relies, in part, on the medical education community developing a shared vision of the Health Advocate (HA) role, designing, implementing, and integrating developmentally appropriate curricula, and considering ethical implications of assessing a role that may be risky to enact. Conclusion: Changes to assessment could be a key driver of curricular change for the HA role, provided implementation timelines and resources are sufficient to make necessary changes meaningful. To truly be meaningful, however, advocacy first needs to be perceived as valuable. Our recommendations are intended as a roadmap for transforming advocacy from a theoretical and aspirational value into one viewed as having both practical relevance and consequential implications.